Factors Affecting Greek Adolescents' Choices of Drinks and Sweets for School Snacks - Papakonstantinou, Smaro; Zarkada, Anna K.; Kapareliotis, Ilias (My University, 2012)
The importance of a healthy diet, especially for teens, is indisputable as it contributes positively to their growth and health and impacts on life-long nutritional patterns. This paper presents the results of an empirical study school lunch and snacking choices in early adolescence. The study utilized a quasi-experimental and questionnaire survey technique involving 300 pupils, of four Athenian high schools, aged between 12 and 14. Results regarding pupils’ dietary requirements showed that pupils adopt a healthy approach and that marketing activities aren’t so much regarding the choice or the brand that they would buy from the canteen. Their behavior is much more influenced from social factors mainly by the parental habits and advices they receive.
Keywords: Consumer behaviour; Teen marketing; Food marketing